2011
DOI: 10.1093/jac/dkq533
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in ftsI gene and  -lactam susceptibility in Portuguese Haemophilus influenzae strains: clonal dissemination of  -lactamase-positive isolates with decreased susceptibility to amoxicillin/clavulanic acid

Abstract: This study shows that the non-enzymatic mechanism of resistance to β-lactams is widespread among H. influenzae isolates in Portugal. Clonal dissemination of BLPACR strains showing high resistance to ampicillin and reduced susceptibility to amoxicillin/clavulanic acid was documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 33 publications
8
35
1
Order By: Relevance
“…In agreement with previous studies [11,12,13], gBLNAR is increasing at a constant rate in respiratory isolates of H. influenzae . The production of β-lactamase was not the main mechanism of β-lactam antibiotic resistance in this study.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous studies [11,12,13], gBLNAR is increasing at a constant rate in respiratory isolates of H. influenzae . The production of β-lactamase was not the main mechanism of β-lactam antibiotic resistance in this study.…”
Section: Discussionsupporting
confidence: 93%
“…However, the Arg517 substitution was not found in either our BLNAR isolates or in previously described H. parainfluenzae isolates (García-Cobos et al, 2013;Tristram et al, 2008). The Val511Ala, Ala530Ser (both near the conserved KTG motif) and Thr574Ala changes have been reported previously in H. parainfluenzae linked to resistance or reduced susceptibility to b-lactams, although often in combination with Asn526Ser, and rarely in H. influenzae (Barbosa et al, 2011;García-Cobos et al, 2013;Kishii et al, 2010;Tinguely et al, 2013). Obviously, in our H. parainfluenzae isolates the possible presence of additional resistance mechanisms affecting susceptibility to b-lactams, such as overexpression of the AcrAB efflux pump or alterations in outer membrane permeability, cannot be ruled out (Kaczmarek et al, 2004).…”
Section: Discussionsupporting
confidence: 59%
“…12,20 b-Lactamase-producing strains (BLPAR) are prevalent globally 13 ; however, the proportion of BLNAR strains has increased since the first report in the early 1980s. 2,9,12,15,22,25,28 Additionally, the incidence of b-lactamase-producing strains with PBP3 mutations (BLPACR strains) that exhibit decreased susceptibility to amoxicillin/clavulanic acid is increasing. 2,6 In South Korea, NTHi strains consisted of 38.9% BLPAR, 29.3% BLNAR, and 8.3% BLPACR from 2000 to 2005.…”
Section: Introductionmentioning
confidence: 99%
“…2,9,12,15,22,25,28 Additionally, the incidence of b-lactamase-producing strains with PBP3 mutations (BLPACR strains) that exhibit decreased susceptibility to amoxicillin/clavulanic acid is increasing. 2,6 In South Korea, NTHi strains consisted of 38.9% BLPAR, 29.3% BLNAR, and 8.3% BLPACR from 2000 to 2005. 18 Another study of nationwide acute respiratory infection during 2005 and 2006 reported 47.2% BLPAR, 6.1% BLNAR, and 5.2% BLPACR strains among NTHi.…”
Section: Introductionmentioning
confidence: 99%